Perception of the healthiness of Pisco macerates in the Barranco district: A study on consumer evaluation - Tejeda-Rodríguez, Isaac (2024)
The study was carried out in the district of Barranco due to its relevance in the offer and consumption of Pisco macerates. Bars were randomly selected based on the Barranco Local Tourism Development Plan for 2020, according to "Ordinance No. 554-2020-MDB." A structured questionnaire with 36 closed questions was used via Google Forms, administered in two sessions, and analyzed in MS Excel. The questionnaire was validated by three experts. The survey took place on Barranco Boulevard over four weekends, interviewing people leaving local bars on Saturdays. The aim was to identify perceptions of regular Pisco macerate consumers, using closed questions for analysis and comparison. The sample included 341 randomly selected individuals. The survey focused on visual, gustatory, and olfactory perceptions related to the Pisco macerate consumption experience. The results showed that visual, gustatory, and olfactory perceptions influence the choice of healthy Pisco macerate consumption. Price and beverage color were determining factors in consumption choices. Additionally, taste was crucial for opting for healthy consumption, although olfactory perception was not a reliable indicator of Pisco authenticity. These findings highlight the importance of educating consumers on identifying quality Pisco and considering visual, gustatory, and olfactory aspects in selecting alcoholic beverages. Ensuring Pisco quality and authenticity is essential to maintaining consumer trust.